Thymoquinone supplementation ameliorates cisplatin-induced hepatic pathophysiology. (October 2021) - Shahid, F; Farooqui, Z; Alam, T; Abidi, S; Parwez, I; Khan, F
Hepatotoxicity is a major dose-limiting side effect of CP chemotherapy besides nephrotoxicity and gastrointestinal dysfunction. TQ, a principal Nigella sativa seed oil constituent, has been shown to improve hepatic functions in various in vivo models of acute hepatic injury. In view of this, the present study aimed to evaluate the effect of TQ against CP-induced hepatotoxicity. Rats were divided into four experimental groups; control, CP, CP+TQ and TQ. Animals in CP+TQ and TQ groups were administered TQ (1.5 mg/kg bwt, orally), with or without a single hepatotoxic dose of CP (6 mg/kg bwt, i.p.) respectively, for 14 days before and four days following the CP treatment. CP induced an upsurge in serum ALT and AST activities, indicating liver injury, as also confirmed by the histopathological findings. CP caused significant alterations in the activities of membrane marker enzymes, carbohydrate metabolic enzymes, and the enzymatic and nonenzymatic components of the antioxidant defense system. TQ supplementation ameliorated all these adverse biochemical and histological changes in CP-treated rats. Thus, TQ may have excellent scope for clinical applications in combating CP-induced hepatic pathophysiology.